Titanium dioxide coatings on magnesium alloys for biomaterials: A review (2017)
Magnesium and its alloys are used for biomaterials in orthopedic applications. Such alloys are still under development, and they are used due to their biocompatibility and mechanical (bone-like) properties that make them suitable to be used as biomaterials. Magnesium has potential to be used in biodegradable implants because of its capacity to support tissue regeneration processes. Therefore, multiple strategies have been developed to enhance magnesium properties. Coatings on magnesium alloys have been used to improve the cytocompatibility and corrosion resistance of magnesium. Particularly, titanium dioxide can be used as coating on magnesium to help regulating degradation rate and overcome some issues when magnesium is inserted into the human body. Accordingly, this paper is a critical review to consolidate the available literature about titanium dioxide coatings on magnesium alloys for potential use as biomaterials. The work focuses on coatings obtained by the sol-gel route as a promising technique for biomedical applications.